2005
DOI: 10.1111/j.1439-0264.2005.00669_105.x
|View full text |Cite
|
Sign up to set email alerts
|

Post‐natal Development of Perineuronal Nets in the Retrosplenial Cortex of Albino Rat

Abstract: The brain extracellular matrix (ECM) has attracted growing interest due to its highly regulated spatiotemporal expression during development and maturation of central nervous system. The present study deals with the post‐natal appearance and transformation into adult distribution patterns of the ECM components related to proteoglycans (PGs) and glycoproteins (GPs) in the retrosplenial cortex (RSC) of albino rats at birth (P0), 1 week (P1), P2, P3, P4, P5, P6, P7 and P8. The differentiating PGs and GPs componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…The distribution of PNs as stained with WFA and VVA, as well as with SBA coincides with previous descriptions performed by using the same lectins, reported in rat (Härtig et al, 1992;Sayed et al, 2002Sayed et al, , 2004Mubarak et al, 2004Mubarak et al, , 2008 and in other species such as mice (Brückner et al, 2000(Brückner et al, , 2003, guinea pig (Ojima et al, 1998), shorttailed opossum (Brückner et al, 1998) or in humans (Bertolotto et al, 1991). In this investigation, the RSC of rats presents several netassociated neuronal subsets, as previously described in many areas of CNS including the cerebral cortex, the hippocampus, the thalamus, the cerebellum, the brain stem and the spinal cord (Celio and Blümcke, 1994).…”
Section: Distribution and Occurrence Of Pnssupporting
confidence: 91%
See 3 more Smart Citations
“…The distribution of PNs as stained with WFA and VVA, as well as with SBA coincides with previous descriptions performed by using the same lectins, reported in rat (Härtig et al, 1992;Sayed et al, 2002Sayed et al, , 2004Mubarak et al, 2004Mubarak et al, , 2008 and in other species such as mice (Brückner et al, 2000(Brückner et al, , 2003, guinea pig (Ojima et al, 1998), shorttailed opossum (Brückner et al, 1998) or in humans (Bertolotto et al, 1991). In this investigation, the RSC of rats presents several netassociated neuronal subsets, as previously described in many areas of CNS including the cerebral cortex, the hippocampus, the thalamus, the cerebellum, the brain stem and the spinal cord (Celio and Blümcke, 1994).…”
Section: Distribution and Occurrence Of Pnssupporting
confidence: 91%
“…Taken together with the previous studies, it is concluded that the basic morphological features of PNs in the RSC was largely identical, although certain heterogeneity is already revealed at the cytochemical and molecular level (Köppe et al, 1997a, b;Sayed et al, 2002Sayed et al, , 2004Mubarak et al, 2008). Notably, distinct differences have been revealed among PNs with respect to the density and intensity of PGs and/or GPs molecules accumulating in the microenvironment of corresponding neuronal cells.…”
Section: General Remarkssupporting
confidence: 71%
See 2 more Smart Citations